Картографічне та інформаційне забезпечення туристичних маршрутів Українських Карпат - Бучко, Жанна Іванівна (Чернівці: Чернівецький національний університет, 2009)
The support of tourist trails with appropriate ethnographic literature and cartographic materials is considered. We analyze the maps and other printed products that produced for the Carpathian tourism.
Cartographic and informational support of tourist trails in the Ukrainian Carpathians
Keywords: Туристичний маршрут; Картосхема; Карта; Картографічні матеріали